HUBUNGAN PERSEPSI SISWA TERHADAP PEMBELAJARAN IPA (FISIKA) DENGAN HASIL BELAJAR KOGNITIF SISWA SMP/SLTP DI KAWASAN PESISIR (KECAMATAN PULAU MERBAU) - Muhamad Sofyan Hadi; Zulirfan Zulirfan; Zuhdi Maaruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was aimed to determine the correlation between students’ perception toward science learning (physics) with students’ cognitive study result. Descriptive study by survey method was use as research method. The data was obtained directly from the sample by using the data instrument which was a quisionnare of students’ perception toward science learning (physic), meanwhile the data of students’ cognitive study result was obtained from mid tern test result. The coefficient of correlation between students’ perception toward science learning (physics) with students’ cognitive study result was 0,013 which was interpreted in very low category. Based on significance value the result was p > 0,05 (0,452 > 0,05), it means that there was no positive and significant relation between students’ perception toward science learning (physics) with students’ cognitive study result on students’ of SMP Negeri in Pulau Merbau sub distric.Key Words: Students’ perception toward science learning (physics), Students’ cognitive study result